Analisis Faktor - Faktor Yang Mempengaruhi Kepatuhan Pajak Wajib Pajak Orang Pribadi (Studi Kasus KPP Pratama Padang) - inggra Sovita (CV. ITTC INDONESIA, 2022)
This study explains the analysis of the factors that influence individual taxpayer tax compliance at Padang Primary Tax Office. In this study the data used is primary data and secondary data. Samples were taken using the random sampling method using the Slovin formula obtained a sample of 100 respondents. The research instrument used was a questionnaire that had previously been tested and fulfilled the requirements for validity and reliability, while for data analysis using multiple linear regression analysis. The processed statistical results assisted with the SPSS 21.0 for windows program show that the effect of independent variables (knowledge of tax (X1), taxation sanctions (X2), and service quality (X3)) on the dependent variable (tax compliance) is able to contribute 82, 9%, while the remaining 17.1% explained other variables not included in this study. The results showed that partially and simultaneously through t-test and f-test the knowledge variable of tax (X1), taxation sanction (X2), and service quality (X3), had an effect on tax compliance on the Pratama KPP Padang